SURVEILANS EPIDEMIOLOGI PENYAKIT DEMAM BERDARAH DENGUE (DBD) DI PUSKESMAS JAYA MUKTI KOTA DUMAI TAHUN 2023-2024 - Masalena, Lisa; Ikhtiyaruddin, Ikhtiyaruddin; Priwahyuni, Yuyun (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: The Dengue Hemorrhagic Fever (DHF) disease is a contagious illness caused by the dengue virus and transmitted by the Aedes aegypti mosquito. The implementation of DHF surveillance at Jaya Mukti Public Health Center has not been effective. This study aims to examine the epidemiological surveillance of dengue hemorrhagic fever (DHF) at Jaya Mukti Public Health Center for the period of 2023–2024. This research employs a qualitative method with a descriptive analytical approach through in-depth interviews, observations, and document reviews. The study involved six informants, including the head of the Jaya Mukti Public Health Center, surveillance officers, DHF program officers at Jaya Mukti Public Health Center, as well as supporting informants such as doctors, nurses, laboratory analysts, and DHF program officers from the Dumai City Health Office. This research was conducted from September to December 2024. The findings indicate that human resources at Jaya Mukti Public Health Center remain inadequate, with only one surveillance officer who is not an epidemiologist. The data analysis activities carried out were only descriptive analysis based on place (sub-district) but not yet by person, place and time. The analysis is only conducted based on location (sub-district) but does not comprehensively consider person, place, and time. Interpretation of data in the form of graphs (diagrams). Dissemination is carried out in workshops and cross-sector meetings, while through social media it is very minimal. It is recommended that Jaya Mukti Public Health Center take immediate measures to provide adequate training and resources, particularly for DHF surveillance. Additionally, supporting applications beyond the Early Warning and Response System (SKDR) should be introduced, and coordination among staff members should be enhanced in data collection process, data processing, data analysis, data interpretation and dissemination of information.Keywords: Epidemiological Surveillance, Dengue Hemorrhagic Fever (DHF), Data Collection Process.